Geo-environmental and socio-economic impacts of artisanal and small-scale mining in Ethiopia: challenges, opportunities, and sustainable solutions - Teku, Degfie (Frontiers in Environmental Science, 2025)
Artisanal and Small-scale Mining (ASM) in Ethiopia plays a vital role in the national economy, contributing significantly to foreign exchange earnings and employment, particularly in rural regions such as Oromia and Benishangul-Gumuz. It provides livelihoods for millions, with many households experiencing enhanced income levels compared to those reliant solely on agriculture. However, ASM is accompanied by substantial geo-environmental and socio-economic challenges that pose risks to both the environment and local communities. These challenges include widespread environmental degradation, pollution, health hazards, and social issues such as child labor and poor working conditions. This review aims to systematically evaluate the key impacts of ASM in Ethiopia, focusing on both its socio-economic benefits and the environmental consequences. A comprehensive literature search was conducted across academic databases including Google Scholar, Scopus, Web of Science, PubMed and Science direct, utilizing keywords like “artisanal mining,” “small-scale mining,” “geo-environmental impacts,” “socio-economic challenges,” “sustainable practices,” and “Ethiopia.” Studies published between 2015 and 2024 were selected based on relevance and rigor, and findings were synthesized into themes covering environmental impacts, health risks, socio-economic benefits, and barriers to sustainable practices. The review reveals that while ASM contributes positively to the economy, particularly in rural areas, it also leads to severe geo-environmental consequences such as soil erosion, mercury contamination, water pollution, deforestation, and biodiversity loss. Additionally, health risks, including respiratory issues and HIV prevalence, and socio-economic challenges, including child labor and high school dropout rates, are prevalent in mining regions. Despite existing regulatory efforts, inconsistent enforcement, limited capacity, and lack of resources hinder the effectiveness of policies. The findings emphasize the need for balanced, sustainable solutions that address the economic benefits of ASM while mitigating its environmental and socio-economic costs. Strengthening regulations, adopting cleaner technologies, improving health and safety standards, and enhancing community engagement are critical to ensuring the long-term sustainability of ASM in Ethiopia.